1998
DOI: 10.1021/js980122d
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Properties of Related Calanolide Compounds with Activity against Human Immunodeficiency Virus

Abstract: The present studies were undertaken to compare the relative pharmacokinetic parameters and bioavailability of two chemically related natural products which are nonnucleoside inhibitors of reverse transcriptase. Both (+)-calanolide A (Cal A; NSC 675451) and (+)-dihydrocalanolide A (DHCal A; NSC 678323) are currently under development for the treatment of HIV infections. HPLC-based analytical assays were developed for both compounds using modifications of a previously published procedure. The assays were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…(+)-Calanolide A is a nonnucleoside RT inhibitor with potent activity against HIV-1. (−)-Calanolide B and (−)-dihydrocalanolide B ( 26 ) possess antiviral properties similar to those of (+)-calanolide A [35, 62]. Both (+)-calanolide A and (+)-dihydrocalanolide A ( 27 ) are stable at neutral pH and currently under development for the treatment of HIV infections.…”
Section: Coumarins and Pharmacological Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…(+)-Calanolide A is a nonnucleoside RT inhibitor with potent activity against HIV-1. (−)-Calanolide B and (−)-dihydrocalanolide B ( 26 ) possess antiviral properties similar to those of (+)-calanolide A [35, 62]. Both (+)-calanolide A and (+)-dihydrocalanolide A ( 27 ) are stable at neutral pH and currently under development for the treatment of HIV infections.…”
Section: Coumarins and Pharmacological Activitymentioning
confidence: 99%
“…Both (+)-calanolide A and (+)-dihydrocalanolide A ( 27 ) are stable at neutral pH and currently under development for the treatment of HIV infections. However, at a pH < 2.0 for 1 h, 73% of the (+)-calanolide A was converted to (+)-calanolide B while 83% of (+)-dihydrocalanolide A was converted to (+)-dihydrocalanolide B [35, 62]. Previously inophyllum A ( 17 ) and (−)-calanolide B ( 25 ) were isolated from the oil of seeds of Calophyllum inophyllum Linn and Calophyllum cerasiferum Vesque, respectively.…”
Section: Coumarins and Pharmacological Activitymentioning
confidence: 99%
“…Cordatolides A (26) and B (27) were about 50 times less active against HIV-1 reverse transcriptase than (+)-calanolide A, indicating that the nature of C-4 substitution is important [54]. (+)-Calanolide A has been extensively studied because of its unique sensitivity/resistance profile [55]; [56], its synergistic effect in combination with other anti-HIV drugs [57] and its pharmacokinetic profile [58], [59], [60], [61], [62]. The interaction of NNRTIs at the hydrophobic non-nucleoside binding site of HIV-1 reverse transcriptase is highly specific.…”
Section: Coumarinsmentioning
confidence: 99%
“…114 was more orally bioavailable than 101 without losing anti-HIV activity (F ¼ 46.8 and 13.2%, respectively). 50 Compound 101 is synthesized from phloroglucinol in five steps and is being investigated for clinical research. [51][52][53][54] A phase IA studies showed that 101 was generally well tolerated in doses up to 600 mg.…”
Section: E In Vitro and In Vivo Study Of Calanolidesmentioning
confidence: 99%